Let me EnterSTEM you! - Pavlova, Pepa; Konova, Stanislava; Borisova, Tatyana; Petkov, Mihail (Open Schools Journal for Open Science, 2019)
The basis of our research lies in introducing the various aspects of the academic disciplines combined under the abbreviation STEM and promoting the benefits they offer to the younger generations. With the assistance of many discussions, social initiatives and projects our group was able to considerably raise general awareness towards the scientific field and succeeded in doing so in a way that is entertaining and captivating to the youth. Here we show the many approaches we took in order to pique the interest towards STEM and towards the different abilities it helps to develop such as interpretation and usage of data, better observational and analytical skills and teamwork. It is vital that on a global scale, the new generations are well-informed on the aforementioned subject and are able to find a deeper understanding of it. We believe that OSOS can give us the opportunity to show these disciplines in an innovative and interesting way